Age and cohort trends in disability among Chinese older adults - Pan, Chaoping; Cao, Na; Kelifa, Mohammedhamid Osman; Luo, Shuren (Frontiers in Public Health, 2023)
Objective: This study aims to examine age and cohort trends in disability among Chinese older adults, and explore the disablement process factors that may explain the cohort trends in disability. Methods: The study used data from five waves of CLHLS. A hierarchical logistic growth model was used to analyze the A-P-C effects and the contributors of cohort trends. Results: ADL, IADL, and FL among Chinese older adults showed increasing age and cohort trends. FL was more likely to result in IADL disability than ADL disability. Among the disablement process factors, gender, residence, education, health behavior, disease, and family income contributed to most of the cohort trends in disability. Conclusions: As facing increasing disability trends among older adults, it is necessary to distinguish age and cohort trends, and develop more effective interventions according to relative contributors to prevent disability among older adults.